FAKTOR-FAKTOR YANG DIPERTIMBANGKAN KONSUMEN DI KABUPATEN PONOROGO, JAWA TUSIUR DALAM MEMUTUSKAN MENGGUNAKAN PASTA GIGI PEPSODENT WHITE (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2003)
The aim of this study is to analyze factors that been considered by consumers in Ponorogo, East of Java when decided using Pepsodent White toothpaste. This study using exploratory approach on 157 household that drawn from the population with Proportional Random Sampling technique and household mother as unit of analysis, and questionnaire as tool for collecting the data. With Factor Analysis as analysis technique, this study propose (6) six .factors, there are: Promotional Mix, Product Image, Product Perception, Healthy Benefits, Packaging, and Product Value. This factors contribute 48,607%.